"Tracking Engagement through Leader" Authentic Leadership's Consequences on Followers' Attitudes: A Sequential Mediated Mode. Issue 10 (26th July 2020) - Malik, Muhammad Faisal; Khan, Muhammad Asif
ABSTRACT: The purpose of this study was to analyze the sequential impact of authentic leadership through relational identification and positive emotions on employee's attitude, i.e. engagement in work related activities. The data was collected through self-administrated questionnaire from 550 employees of the public sector organizations. The results suggested that authentic leadership has significant impact on employee's relational identification, which further leads to positive emotions and employee engagement.